CT Pulmonary Angiography Utilization in the Emergency Department: Diagnostic Yield and Adherence to Current Guidelines. (November 2015) - Perelas, Apostolos; Dimou, Anastasios; Saenz, Augustina; Rhee, Ji Hyun; Teerapuncharoen, Krittika; Rowden, Adam; Eiger, Glenn
The aim is to investigate the patterns of computed tomography pulmonary angiography (CTPA) use and adherence to current guidelines. Medical records of patients investigated with CTPA for pulmonary embolism (PE) in a single academic hospital from January 2011 until December 2012 were reviewed. Wells scores were calculated retrospectively by researchers blinded to the results of the CTPA. "Avoidable imaging" was defined as imaging performed against current recommendations of the European Society of Cardiology or the PIOPED investigation group. A total of 646 patients underwent testing; 61 cases of PE were diagnosed (9.4%). Potentially avoidable imaging was performed in 49.5% and 71.5% of patients, depending on the criteria used; 11.5% of imaging studies were performed in low-risk patients with negative D-dimer assays. There is evidence of CTPA overuse and D-dimer underuse. Adherence to guidelines and appropriate use of D-dimer assay might reduce avoidable imaging and ionizing radiation exposure.